溶融アルミニウムめっき鋼板のリチウムイオン二次電池用集電体としての可能性 - 内舘, 道正; 佐々木, 悟; 多田, 有矢; 宇井, 幸一; 阿部, 孝裕; 工藤, 尚範; 小浦, 節子; 辻村, 太佳夫; 齋藤, 良平; 門磨, 義浩 (Hyōmen gijutsu, 2016)
For conventional organic electrolytes used in lithium-ion secondary batteries, we evaluated the electrochemical characteristics of hot-dipped aluminum（including 9 mass% silicon）-coated steel sheet, after rolling, as a current collector. Cyclic voltammograms clearly showed coupled redox peaks for potentials of 0-0.25 V（vs. Li/Li＋）. The redox peaks were attributed to reduction and oxidation reactions corresponding to insertion and extraction reactions of the Li＋ ion into and from Al and Si. Oxidation current at higher potential was observed from about 3.25 V, indicating an electrochemical window of 3.00 V for potentials of 0.25-3.25 V. Subsequent EDX results revealed that the atomic concentration of Si in the aluminum layer decreased drastically after anodic polarization, suggesting the dissolution of Si. Using hot-dipped aluminum-coated steel sheet, after rolling, as a current collector for a positive electrode was inferred to be difficult. Using Li4Ti5O12 and a Li4.3Ti5O12 carbon composite for charge-discharge tests, we evaluated the application of a hot-dipped aluminum-coated steel sheet, after rolling, as a current collector for lithium-ion secondary batteries. Results show that the material can be used as a current collector for a Li4.3Ti5O12 carbon composite negative electrode.